Spiranoid Withanolides from Jaborosa odonelliana and Jaborosa runcinata - Cirigliano, Adriana Monica (2005)
Two new spiranoid withanolides, (20R,22R,23R)-12β,17β,22- trihydroxy-1-oxo-12,23-cycloergosta-2,24-dien-26,23-olide (3) and (23R)-5α,6β,12β,21-tetrahydroxy-1,22-dioxo-12,23-cycloergosta-2, 17,24-trien-26,23-olide (4) were isolated from plants of Jaborosa odonelliana and Jaborosa runcinata, respectively. Compounds 3 and 4 were characterized by a combination of spectroscopic methods (1D and 2D NMR, MS) and molecular modelling.